Assessment of Diesse Ves-matic automated system for measuring erythrocyte sedimentation rate. - Caswell, M (1991)
Measurement of the erythrocyte sedimentation rate (ESR) using a closed tube system reduces the biohazard risk to laboratory staff. The Diesse Ves-matic system offers manual or vacuum collection of blood into plastic tubes, automated mixing of the sample, and automated reading of the end point after 20 minutes of sedimentation. This system was compared with the 1977 Westergren ESR method of the International Council for Standardization in Haematology (ICSH) and with the 1988 ICSH undiluted ESR method. Manually collected Ves-matic samples showed good agreement with ICSH values, although there was a tendency to false low results at low ESR values which may represent dilution of plasma protein with excess citrate. Vacuum collected Ves-matic samples also showed good agreement with ICSH values, although there was a tendency to false high results which may reflect a change in the blood: citrate ratio caused by loss of anticoagulant diluent or vacuum from plastic tubes during storage. The Diesse Ves-matic system incorporates several improvements over previous technology and offers a safer, quicker, and more standardised ESR.